An Artificial Thermal Nociceptor Based on Xanthan Gum‐Gated Synaptic Transistors to Emulate Human Thermal Nociception - Fang Zhou Li; Hong Rui Liu; Jian Miao Guo; Xin Yi Zhou; Ke Kang Liu; Lin Zi Liang; Xin Yi Pei; Fei Chi Zhou; Feng Huang; Hong Wang; Yang Hui Liu (Advanced Intelligent Systems, 2022)
Nociceptors are kinds of sensory neurons that send warning information to the central nervous system in response to noxious stimuli. Thermal nociception happens as the thermal stimulus exceeds 45 °C as this temperature is perceived to be potentially harmful. Simulating this function is of great significance to developing bioinspired electronic skins and humanoid robots, which thus creates more demands for electronic devices that can simulate thermal nociception. Herein, an artificial thermal nociceptor (ATN) is fabricated by integrating a temperature sensor and a synaptic transistor, which can simulate the thermal pain threshold of the human body and operates in a very similar way as the transient receptor potential vanilloid 1 (TRPV1). For this ATN, the function of temperature sensing is realized by a graphite–polydimethylsiloxane (Gr–PDMS) composite temperature sensor, and the synaptic functions, as well as nociceptor features, are emulated through a synaptic transistor using xanthan gum polysaccharide electrolyte as gate dielectric, providing energy‐efficient building blocks for brain‐inspired computation systems. In a word, the ATN proposed can help to open a new avenue and provides more possibilities in the design of artificial sensory systems with the functions of temperature perception and thermal feedback.